Relationship between annual soil erosion and surface runoff in Wadi Hanifa sub-basins - Alzahrani Hassan (Open Geosciences, 2023)
Soil erosion is the major environmental risk that causes topsoil loss, which decreases fertility in agricultural land. Spatial estimation of soil erosion is essential for conserving land resources and for developing control plans. This study evaluated soil erosion in 17 sub-basins of the Wadi Hanifa catchment using the Gavrilović model. The soil erosion rate is categorized into three classes based on the annual volume of rainfall and runoff. About 21% of the drainage area of Wadi Hanifa is affected by erosion severity, and 33% of the area is affected by severe erosion. The correlation obtained between the annual soil erosion and annual volumes of rainfall and runoff is significant. It is concluded from the results that the drainage area of the north-western part suffers from a high soil erosion risk. The NRCS-CN and erosion predict that the Gavrilović model can be applied for estimating and analyzing the spatial distribution of soil erosion over more drainage watersheds in Saudi Arabia. Now, the GIS techniques are one of the best tools for developing the conservation and management planning processes of soil resources.